The Relationship between Personality Traits and Occupational Self-Efficacy with Career Interests among University Students - Abdullah, Abdullah Seif (2001)
This study investigated the relationship between personality traits and occupational self efficacy with career interests among Malaysian university students. The demographic factors associated with students' occupational self-efficacy and career interests were also determined. The study had provided more insights on students' behaviour that could enhance the alleviation of social and academic maladjustment among students and increase their academic achievement. In addition, the findings of this study were likely to enhance job satisfaction, quality services, and productivity. The research questions and hypotheses determined the following objectives of the study: 1. The identification of students' occupational self-efficacy expectations, career interests patterns, prevalent personality traits and their relationship. 2. The relationship between personality traits, occupational self-efficacy, and career interests with the extraneous variables. 3. The relationship between personality traits and occupational self-efficacy with career interests after controlling for the demographic variables. The population of the study comprised the second and third year Malaysian undergraduate students. Accordingly, based on the knowledge disciplines, 238 subjects were selected from UPM, HUM, and UTM using the cluster random sampling. The Occupational Self-Efficacy Scale (OSES), Vocational Preference Inventory (VPI), and Personality Research Form (PRF) were used in the data collection to measure occupational self-efficacy, career interests, and personality traits respectively. The computer program software, Statistical Package for Social Sciences (SPSS) was used in the data analysis. The statistical techniques used were Pearson and Point-Biserial correlation, ANOVA, MANOVA, and the Multiple Regression.